Production of ZnS based supercapacitor electrode material from ferrochrome ash waste - Aydin, Ozan; Birol, Burak; Gencten, Metin (SPRINGER HEIDELBERG, 2023)
In the present study, ZnS was recovered from ferrochrome ash (FCA) waste using a hydrometallurgical process for the first time in the scientific literature, and it was utilized as an electrode material for asymmetric-type coin cell supercapacitors. FCA was initially leached with H2SO4 and HNO3 solutions with varying liquid: solid (L: S) ratios, acid concentrations, and leaching times. The optimal leaching parameters were 0.25 M as HNO3 concentration, 50:1 as L: S ratio, and the shortest leaching period of 5 min obtained, which resulted in 70.71% wt. Zn leaching efficiency (LE). Then, the pregnant liqueur was mixed with Na2S solutions, to precipitate ZnS. Afterward, an anode to be used in coin cell type supercapacitor was produced by mixing ZnS, carbon black, and PVDF in varying compositions. The obtained coin cell was characterized by electrochemical techniques. The highest specific capacitance value was determined as 71 mF.cm(-2) at a scanning rate of 10 mV/s in a supercapacitor containing 70% wt. ZnS anode, however the highest capacitance retention (92.82%) was obtained after 1000 cycles of CV test for the 60% wt. ZnS including anode.
Keywords: Recycling; Hydrometallurgy; Ferrochrome ash; Energy storage; Supercapacitor; ARC FURNACE DUST; ELECTROCHEMICAL PROPERTIES; FACILE SYNTHESIS; COBALT SULFIDE; ZINC RECOVERY; PERFORMANCE; ACID; NANOPARTICLES; PRECIPITATION; BEHAVIOR; Chemistry; Electrochemistry; Physics